FRI0526 Quality of Ultrasound-Guided Synovial Biopsies Performed in Clinical Practice. (15th July 2016) - Najm, A.; Bart, G.; Heymann, M.-F.; Maugars, Y.; Le Goff, B.
Abstract : Background: Synovial tissue is the principal target and end organ involved in the pathogenesis of multiple articular disease processes. Histological and bacteriological analyses of synovial tissue (ST) are useful in clinical practice for the diagnosis of undifferentiated arthritis. Ultrasound (US) allows an evaluation of the synovial thickness and inflammation. It also helps to perform real-time synovial biopsy and detect nearby structures such as tendons, nerves and vessels. Objectives: The aim of this study was to assess quantity and quality of synovial tissue obtained by ultrasound guided synovial biopsies, in clinical practice. Methods: We retrospectively analysed all synovial biopsies performed between January 2007 and December 2014 in the Rheumatology Department of Nantes University Hospital. Synovial biopsies were performed under real-time US guidance (Philips HD11 XE) using a core biopsy needle with a 14 or 16G calibre semi-automatic Tru-cut needle. This technique allows to collect multiple synovial samples during a single procedure. Hematoxylin and eosin stained slides were analysed by one operator (AN), blindly from clinical data. Size, area, presence/absence of synovial tissue, presence/absence of lining layer, other types of tissues were assessed and compared to pathologist's analysis (gold standard). Results: 75 biopsy procedures were analysed (73 patients). 125 samples were available for analysis corresponding to a median number of samples taken per patient of 1 (IQR 1–3). Mean length and width of the biopsy samples were 6.34 millimetres (mm) (±3.60) and 1.70 mm (±0.77) respectively. The mean total area of the samples was 8.77 mm 2 . Biopsies showed synovial tissue at the histological examination in 102 samples (80.1%). The average area of synovial tissue in these samples was 6.36 mm 2 corresponding to 72.5% of the total area of biopsied tissue. The other types of tissue present on these biopsies were connective tissue in 101 cases (80.8%), adipose tissue in 42 cases (33.6%), tendon in 14 cases (11.2%) and fibrin in 24 cases (19.2%). The 23 sample retrieving no synovial tissue were composed of fibrin in 15 cases (12%), conjunctive and adipose tissue in 17 cases (13.6%), tendon in 3 cases (3.15%), cartilage in 3 cases (3.15%) and muscle in one case (0.8%). Synovial lining layer was found in 92.6% of the successful biopsies. Interobserver reliability for presence/absence of synovial tissue between AN and the pathologist was high with a kappa coefficient of 0.90 (95%CI =0.763 to 1). Conclusions: Our study is the first to assess quality and quantity of synovial tissue obtained by ultrasound guided biopsy, in the clinical setting. In 80% of the biopsy procedures, quantity and quality of the synovial tissue were high enough to allow a proper histological examination. Given the fact that conjunctive and adipose tissues as well as fibrin were frequently seen on histological examination, retrieving a minimal number of 2 samples per patient appears to be required for appropriate pathology assessment in the clinical setting. Disclosure of Interest: None declared